(untitled) (Práxis Educativa, 2024)
This article identifies and problematizes the contribution that Portuguese public universities (PPU) have made in the field of capacity building and in the area of ​​evaluation of science education projects within the scope of development cooperation, specifically in Timor-Leste and São Tomé and Príncipe. Methodologically, this research is both qualitative and quantitative. In the first phase, the content analysis of the different strategic plans of the PPU was carried out; in the second phase, the scientific production of these universities was analyzed with an analysis of the respective institutional repositories. A list of keywords was used: evaluation, cooperation, science education projects or education projects, Timor-Leste and São Tomé and Príncipe, defined strategically to better understand which theoretical axis(axes) is(are) presented, or not, as area(s) of focus. With this, the weaknesses and strengths that serve as support for future investigations and cooperation agreements were perceived. In general, it is concluded that the PPU have contributed little to the development of investigations at the intersection of theoretical axes such as evaluation, cooperation and science education projects, even though cooperation, in general, appears to be more significant in the Santomean context than in the Timorese. Keywords: Evaluation for cooperation. Science education projects. Portuguese public universities.